2017
DOI: 10.1186/s40413-016-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact on quality of life on families of children on an elimination diet for Non-immunoglobulin E mediated gastrointestinal food allergies

Abstract: BackgroundThe impact on health related quality of life (HRQL) has been well studied in children with Immunoglobulin E (IgE)-mediated food allergy. However limited data exists on related quality of life (QOL) of families who have a child suffering from food protein induced non-IgE mediated gastrointestinal allergies. We aimed to establish the QOL of families with children at the beginning of following an elimination diet for non-IgE mediated gastrointestinal food allergies.MethodsA prospective, observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
0
38
0
1
Order By: Relevance
“…Studies report that parents of food allergic children have increased levels of anxiety and poorer quality of life; therefore, parental anxiety rather than the organic disease present in the child may at times drive the feeding difficulty. 41…”
Section: Persistent Feeding Difficulty Amentioning
confidence: 99%
“…Studies report that parents of food allergic children have increased levels of anxiety and poorer quality of life; therefore, parental anxiety rather than the organic disease present in the child may at times drive the feeding difficulty. 41…”
Section: Persistent Feeding Difficulty Amentioning
confidence: 99%
“…Additionally, complete avoidance of all nuts is not necessarily recommended anymore, and only those nuts reacted to should be eliminated from the diet [ 54 ]. In addition to nutritional consequences of food allergy, it is known that children and families with food allergies experience a decreased quality of life across a number of domains, which can create anxiety and lead to avoidance of social situations [ 55 , 56 , 57 , 58 ]. Hence, it is suggested that liberalisation of the diet, when appropriate and safe, will increase both quality of life and nutritional intake.…”
Section: The Role Of Diet In the Management Of Food Allergymentioning
confidence: 99%
“…relevance, and also that the proteins remaining in soy lecithin have little antigenicity with regard to soybean allergy (11,(19)(20)(21)(22)(23) . Elimination diets, particularly with respect to the increasing number of foods that require avoidance, reduce the quality of life of families and children (2,(24)(25)(26)(27) The inclusion of soya lecithin in children with a soya allergy is often determined by the healthcare professional based on a risk assessment. In non-IgE-mediated cow's milk allergy, the data indicate 30-64% of children have a concomitant soya allergy (5,6) .…”
Section: Discussionmentioning
confidence: 99%